Health-Related Quality of Life After TBI: A Systematic Review of Study Design, Instruments, Measurement Properties, And Outcome Health Related Quality of Life in Adults After Burn Injuries: A Systematic Review and Meta-Analysis - Aljahdali, Fahad Hameed; ALSOBHI, MOSTAFA MOHAMMADSAEED S; Althobaiti, Bandar saeed; alsobhi, Yahya obedullah; Al hasani, Abutaleb Ghareeb Ibrahim; Al-Youbi , Talib Mohsen; alharbi, Ahmad jazaa; Alrubaain, Afnan ibraheeim; Almalki , Sarah Ayed Mohammed; AL motairi, Suliman kalawi; AL QAHTANI, HUSSEN SALEH AHMED (Journal of Ecohumanism, 2024)
Background: Psychological and cognitive disturbances resulting from falls, road traffic accidents, other incidents, and attacks haven’t been sufficiently identified within the healthcare and social level in Japan. Aim: to measure the outcome Health-related quality of life in adults following burn injuries. Materials and methods: This systematic review was conducted on five studies. The PRISMA statement, which stands for Preferred Reporting Items for Systematic Reviews and Meta-analyses, has been considered during the reporting process. Key parameters analyzed included TBI, health-related quality of life, and burn injuries. Results: Our meta-analysis for QOL after traumatic brain injury was assessed in three studies totaling 385 patients; our pooled MD and 95% CI were 29.07 [16.03, 42.12]. Major heterogeneity was detected among our pooled studies for this outcome with chi-p < 0.001 and I² 100%. Our meta-analysis for the HADS scale after traumatic brain injury was assessed in three studies totaling 984 patients; our pooled MD and 95% CI were 4.78 [1.57, 7.99]. Major heterogeneity was detected among our pooled studies for this outcome with chi-p < 0.001 and I² 100%. Conclusion: The analysis of overall QOL and general health revealed significant variability across studies, as did the assessment of psychological well-being, physical capacity, and social relations. Additionally, the Hospital Anxiety and Depression Scale (HADS) also showed considerable heterogeneity across the studies. These findings underscore the challenges in measuring the influence of TBI on health-related QOL and suggest the need for further research.